PEMBUATAN BISKUIT DARI PASTA UBI UNGU (Pasta Diproses Menggunakan Rotary Evaporator) - Yerizam, Muhammad; Ningsih, Anis Wahyu (KINETIKA, 2020)
The provision of breast milk (ASI) cannot optimally fulfill the increasing nutritional needs of infants after entering the age of 6 months, so it must be balanced with complementary feeding of breast milk (MP-ASI). One of the foods that contain lots of nutrients for babies is purple sweet potato. Purple sweet potato can be processed into a paste for raw materials for making biscuits as complementary food for ASI (MP-ASI). The aim of this research is to make biscuits according to SNI No. 01-7111.2-2005 using raw material for purple sweet potato paste. The concentration of bait used was 62.5%, 55.5% and 50%. Purple sweet potato paste is made using a rotary evaporator. The results showed that the optimum operating conditions for the rotary evaporator in producing the paste were at a feed concentration of 55.5%, the viscosity, density and water content values obtained were 311.4176 mPa.s, 1.0885 gr / mL and 57.7578%. The paste produced from the rotary evaporator is then used to make purple sweet potato biscuits. The analysis showed that the carbohydrate, protein, fat and water content were 39.30%, 8.42%, 20.35% and 16.05%. The purple sweet potato biscuits that were produced were close to SNI No. 01-7111.2-2005.